Exploring service and support needs in postgraduate education towards the higher education quality - Zainal Abiddin, Norhasni; Ismail, Affero
Students’ support is needed in postgraduate education embracing many service areas towards quality education. In achieving excellent graduates for national transformation reality, it needs to be addressed at all levels including departmental and institutional. It is vital to create suitable environment for students’ studies to ensure the sustainable development and execution of outstanding research outcome. The paper identifies that one of the important factors in students’ development is to create proper support and services. Thus, a qualitative analysis has been conducted to postgraduate student to discover the main concern of the support and services offered in a Malaysian public university. This study involved semi-structured interviews and the sample was self-selecting. The study disclosed the most important needs and deprived services that should be improved.